Seroprevalence of bovine viral diarrhea virus (BVDV) in cattle in the Northern, Northcentral, Central, and Southern provinces of Sri Lanka - Weerasekara, W. M. G. K.; Dhananjaya, W. M. C.; Ashinika, W. M. D.; Wijewardana, V.; Kangethe, R. T.; Kalupahana, A. W.; Mahakapuge, T. A. N. (Frontiers in Veterinary Science, 2025)
Bovine Viral Diarrhea Virus (BVDV) is a highly significant cattle pathogen with economic impacts that lead to reproductive failures, immunosuppression, and low productivity. This research paper examined the seroprevalence of BVDV in four Provinces in Sri Lanka, namely Northern, North Central, Central and Southern, which represents both wet and dry agro-climatic zones. In total, 178 archived bovine serum samples collected during 2022 and 2023 were tested to evaluate BVDV-specific antibodies with an indirect ELISA. Numerically, the wet zone had 14.7% seropositive (10/68), and none of the cattle in the dry zone were found to be positive (0/110). The prevalence may be higher in the wet zone due to grazing practices and shared water sources, which facilitate viral transmission. This paper highlights the need of constant surveillance to monitor the seroprevalence while establishing methods to detect BVDV antigens among the local cattle populations. The importance of maintaining vaccine records are needed to prevent the interference with surveillance studies. Further research with larger and more geographically diverse sampling, including buffaloes, are recommended to clarify the national status and economic impact of BVDV infection in Sri Lanka.